2013
DOI: 10.1016/j.neuron.2013.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Nanoscopy of Inhibitory Synapses: Counting Gephyrin Molecules and Receptor Binding Sites

Abstract: The strength of synaptic transmission is controlled by the number and activity of neurotransmitter receptors. However, little is known about absolute numbers and densities of receptor and scaffold proteins and the stoichiometry of molecular interactions at synapses. Here, we conducted three-dimensional and quantitative nanoscopic imaging based on single-molecule detections to characterize the ultrastructure of inhibitory synapses and to count scaffold proteins and receptor binding sites. We observed a close co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

31
290
2
10

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 203 publications
(333 citation statements)
references
References 50 publications
(98 reference statements)
31
290
2
10
Order By: Relevance
“…On average, 200 copies of gephyrin molecules were found per synapse, though the absolute figures and cluster size were highly dependent on the type of sample. These authors also showed that the other major inhibitory receptors in brain (GABA A receptors) colocalized with gephyrin [23]. In a very recent extension of that study, gephyrin was shown to form scaffolds which act as shallow energy traps ( 3 kBT) for glycine neurotransmitter receptors [24].…”
Section: Imaging Postsynaptic Proteinsmentioning
confidence: 87%
See 1 more Smart Citation
“…On average, 200 copies of gephyrin molecules were found per synapse, though the absolute figures and cluster size were highly dependent on the type of sample. These authors also showed that the other major inhibitory receptors in brain (GABA A receptors) colocalized with gephyrin [23]. In a very recent extension of that study, gephyrin was shown to form scaffolds which act as shallow energy traps ( 3 kBT) for glycine neurotransmitter receptors [24].…”
Section: Imaging Postsynaptic Proteinsmentioning
confidence: 87%
“…They could also follow dynamic changes undergone by the nanoclusters. Similarly, Specht et al [23] used a combination of PALM/STORM microscopies to quantify the abundance of the peripheral, non-receptor protein gephyrin, labeled with the fluorescent proteins Dendra2 and mEos2, in inhibitory synapses of a knock-in mouse expressing mRFP-gephyrin [23]. On average, 200 copies of gephyrin molecules were found per synapse, though the absolute figures and cluster size were highly dependent on the type of sample.…”
Section: Imaging Postsynaptic Proteinsmentioning
confidence: 99%
“…34 Recently, quantitative nanoscopy was used to calculate the number of gephyrin molecules and inhibitory synaptic receptor binding sites. 35 Purely GABAergic synapses were found to harbor~40-500 gephyrin molecules and 30-200 GABA A receptors organized in microclusters. In contrast, spinal cord synapses, which contain both GlyRs and GABA A receptors, showed a twofold higher packing density of gephyrin, suggesting that the binding to GlyRs affected the compactness of the hexagonal gephyrin lattice.…”
Section: Expression and Localizationmentioning
confidence: 99%
“…In contrast, spinal cord synapses, which contain both GlyRs and GABA A receptors, showed a twofold higher packing density of gephyrin, suggesting that the binding to GlyRs affected the compactness of the hexagonal gephyrin lattice. 35 Moreover, although the phosphorylation of gephyrin is known to modulate its binding affinity, clustering and receptor association, it is not yet known whether increased gephyrin cluster stability correlates with tighter packaging within the lattice. 35 Overall, these data suggest that gephyrin is tightly packed beneath the GlyR-containing postsynaptic membrane.…”
Section: Expression and Localizationmentioning
confidence: 99%
See 1 more Smart Citation